2021
DOI: 10.1101/2021.03.17.21253801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on surgical procedures in Brazil: a descriptive study

Abstract: BackgroundThe COVID-19 pandemic has deeply affected medical practice, and changes in healthcare activities were needed to minimize the overload and avoid healthcare systems collapse. The aim of this study was to evaluate the impact of the pandemic on surgical procedures in Brazil.Materials and MethodsWe conducted a descriptive study of the number of hospitalizations for surgical procedures in Brazil from 2016 to 2020. Data were collected from the Brazilian Department of Informatics of the Unified Health System… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…Our study found a statistically significant difference in the number of admissions for surgery in oncology across the study period, a 4.5% decrease, which is close to the 5.6% reduction reported by the study of Luizeti et al [ 23 ], inferring that Brazil showed a tendency to opt for surgical intervention for most oncology cases. This is because the management of oncological cases is crucial for health systems as treatment delays have severe consequences for patients and society.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study found a statistically significant difference in the number of admissions for surgery in oncology across the study period, a 4.5% decrease, which is close to the 5.6% reduction reported by the study of Luizeti et al [ 23 ], inferring that Brazil showed a tendency to opt for surgical intervention for most oncology cases. This is because the management of oncological cases is crucial for health systems as treatment delays have severe consequences for patients and society.…”
Section: Discussionsupporting
confidence: 88%
“…This is in agreement with the findings of this study, indicating a decreased number of admissions and LOS for non-urgent surgeries in the same period, especially for endocrine surgery, which recorded the highest decrease (19.9%), followed by oral and maxillofacial surgery (17.3%). Given the elevated risk of COVID-19 infection in immunocompromised patients, for example, those undergoing oncological surgery, guidelines recommended delaying surgeries if feasible to minimize intrahospital COVID-19 transmission and making decisions based on the pandemic's impact on the health facility [ 23 ]. It is worth noting that surgeons performing more invasive procedures, such as ear, nose, and throat, thoracic, foregut, and endoscopy, were at higher risk of contracting COVID-19 during the pandemic due to the aerosol transmission of the virus [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies conducted in Brazil are descriptive analysis, not accounting for causal effects between the reduction of elective procedures and the COVID-19 pandemic. That said, a descriptive study compared the average number of elective procedures from 2016 to 2019 with 2020, suggesting a reduction of 34.82% (95% CI 34.73–34.90) 20 . Another descriptive study conducted in the state of Ceará, Brazil, found a reduction of 89.3 and 67.9% in the number of transplants and organ donations, respectively, comparing Apr-Jun/2020 with Apr-Jun/2019 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies showed the potential underreporting of deaths by COVID-19 in Brazil. 50,51 There was an increase of unexpected deaths by natural causes in regions severely inflicted by COVID-19. 50, 51 The excess of deaths can be associated with indirect consequences of the COVID-19 pandemic, such as health care shortages or overburdened health care systems.…”
mentioning
confidence: 99%
“…50,51 There was an increase of unexpected deaths by natural causes in regions severely inflicted by COVID-19. 50, 51 The excess of deaths can be associated with indirect consequences of the COVID-19 pandemic, such as health care shortages or overburdened health care systems. 52 However, although the number of elective surgeries decreased 34% in 2020, the urgent procedures decreased only 1.1%.…”
mentioning
confidence: 99%